Segmentasi dan Positioning Jasa Pendidikan di MAN Yogyakarta III - Atika Atika; Imam Machali (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
This research discusses about the segmentation and the position of education services in order to determine its implementation in Islamic Educational Institutions. This is a qualitative research with the primary respondent for all the school community who are involving in the marketing process. This research used phenomenological approach, while the data was collected using observation method, indepth interviews, documentation and triangulation. The results indicates that: (1) MAN Yogyakarta III defines market segmentation by applying multiple segmentation approach, namely: (a) demographic segmentation, (b) geographic segmentation, (c) psychographic segmentation, (d) psychological segmentation, and (e) benefit segmentation. (2) MAN Yogyakarta III determines the position of educational services in the academic field with the development of the brand “Madrasah of The Champions” that leads to the vision of MAYOGA, namely Ultraprima. Market segmentation is the first thing that must be accomplished by the madrasah to achieve optimum marketing results, followed by positioning. Position or image formed by the institutions has a dominant role in influencing public attitudes toward madrasah.